Periprosthetic Joint Infection of the Hip and Knee - Springer, Bryan D.; Parvizi, Javad; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Periprosthetic Joint Infection of the Hip and Knee is a practical reference for the diagnosis and treatment of total joint infections following hip and knee arthroplasty. In addition to useful chapters presenting common tests and algorithms used for diagnosis, the book gives background on the epidemiology, risk factors, and prevention strategies of periprosthetic joint infection. Additionally, practical clinical information is given, including antibiotic treatment strategies and delivery methods and medical optimization techniques for physicians to follow for patient care and follow-up. Covering a topic that is currently underrepresented in the medical literature, Periprosthetic Joint Infection of the Hip and Knee will be useful to orthopedic surgeons, rheumatologists, and other physicians involved in the care of patients with hip and knee prosthetic implants.
Epidemiology of Total Hip and Knee Arthroplasty Infection -- Risk Factors for Periprosthetic Joint Infection -- Prevention of Periprosthetic Joint Infection -- Medical Optimalization of Patients Prior to Surgery -- Diagnosis of Periprosthetic Joint Infection: An Algorithmic Approach to Patients -- Intraoperative Tests to Aid in Diagnosis of Periprosthetic Joint Infection -- Biofilm-Related Periprosthetic Joint Infection -- Microbiology of Periprosthetic Joint Infection -- Antibiotics in Treatment of Periprosthetic Joint Infection -- PMMA and Antimicrobial Delivery -- Prosthetic Retention: Treatment Options -- Single-Stage Exchange for Treatment of Periprosthetic Joint Infection -- Two-Stage Exchange Hip Arthroplasty: Static Spacers -- Two-Stage Exchange Hip Arthroplasty: Articulating Spacers -- Two-Stage Exchange Knee Arthroplasty: Static Spacers -- Two-Stage Exchange Knee Arthroplasty: Articulating Spacers -- Knee Arthrodesis -- Resection Arthroplasty and Hip Joint Fusion -- Above-Knee Amputation -- Post-Operative Management of Periprosthetic Joint Infection.
Keywords: Medicine; Orthopedic surgery; Rheumatology; Sports medicine; Medicine & Public Health; Surgical Orthopedics; Sports Medicine; Rheumatology